Improving the impact resistance of the multilayer composites using nanoparticles. Issue 6 (3rd June 2023) - Hoseinlaghab, Sadegh; Farahani, Mohammadreza; Safarabadi, Majid
Abstract: The application of composites in various industries has grown considerably. The relatively high cost of Low-Velocity Impact (LVI) tests and the limitation in data collection due to the short time of this test, on one hand, and previous reports of the conformity of Quasi-Static Indentation (QSI) test results to LVI test results, on the other hand, have convinced researchers to use QSI instead of LVI. The present research investigates the effect of various percentages of nanoclay (because of their cost-effectiveness) on the impact properties of glass-epoxy composite and has used the QSI test to predict the behavior of this nano-composite. For the homogeneous distribution of nanoclay in the resin, a mechanical and an ultrasonic stirrer were used, and the EDAX image of the nano-resin cross-section confirms the success of this process. The QSI test results showed that adding 3% nanoclay to the glass-epoxy composite improves energy absorption by 18%. Moreover, the SEM images indicated that the samples containing 7% nanoclay had deteriorated mechanical properties due to nanoparticle agglomeration. In the end, experimental and numerical LVI tests were performed on the samples containing zero and 3% nanoclay to evaluate the agreement between QSI and LVI test results. The increase in the maximum force and elastic energy and the decrease in the damping ratio and residual deflection all indicate the positive effect of clay nanoparticles on impact-resistance. Numerical results were also very well matched with experimental ones.